Complete chloroplast genome sequencing of Pseudocodon convolvulaceus, a medicinal herb from Qinghai-Tibet Plateau in China - Likuan Liu; Qiwen Li; Jingxuan Du; Weibo Yuan; Rui Sun; Haoyu Liu; Jinping Li (PLoS ONE, 2025)
As a medicinal plant on the Qinghai-Tibet Plateau, Pseudocodon convolvulaceus has garnered significant attention due to its rich medicinal value, demonstrating notable anti-inflammatory and antioxidant activities. To elucidate the characteristics of the chloroplast genome and the phylogenetic position of Pseudocodon convolvulaceus, as well as to explore its genetic structure and evolutionary significance, the complete chloroplast genome was sequenced, assembled, annotated, and compared with the published genomes of the Campanulaceae family. This analysis provides insights into gene content, structural variation, and phylogenetic relationships. A phylogenetic tree was constructed based on the chloroplast genomes of 19 published Campanulaceae species, utilizing two Asteraceae species as outgroups. The results indicated the following: (1) The chloroplast genome of Pseudocodon convolvulaceus is 183,616 bp in length, featuring a typical tetrad structure with a GC content of 38.7%. A total of 134 genes were annotated, comprising 89 protein-coding genes, eight rRNA genes, and 37 tRNA genes, with 12 genes containing one intron and three genes containing two introns. (2) The chloroplast genome includes 67 SSR loci, predominantly single nucleotide repeats, which account for 40% of the total. (3) The genome comprises 64 synonymous codons, including 30 high-frequency codons (RSCU > 1), with 29 of these high-frequency codons ending in A/T, representing 96.7%. This suggests a tendency for high-frequency codons in the chloroplast genome of Pseudocodon convolvulaceus to terminate with A/T. (4) Phylogenetic analysis revealed that Codonopsis minima, Codonopsis lanceolata, Codonopsis pilosula, and Codonopsis tsinlingensis are closely related to Pseudocodon convolvulaceus. The findings of this study enhance our understanding of the genetic basis of this species and its potential applications in drug research, thereby facilitating the use of this genomic resource for conservation strategies and phylogenetic analysis.